Multicultural Discourse in Indonesia: Cultural Response Education in the Classroom for Children - Hapsari, Sukma Dewi; Zahro, Saffanah (Universitas Islam Negeri Alauddin Makassar, 2021)
Education is a process of activities carried out to live a good life and can also be said to be an activity of honing human resources (human resources) to gain expertise in the social field and the development of a good person to make a strong interpersonal relationship with the cultural environment of the surrounding community. On that basis, why education cannot be far from the culture or culture of a place it occupies, as the goal of education so far, namely, to hone taste, initiative and work. The achievement of these educational goals depends on how the culture is conveyed in the classroom, so this is where the role of multicultural education will become an intermediary for the development of human resources who have strong and good characters. This study aims to describe several things, namely as follows: (1) Culture-based learning; (2) Application of Cultural Learning to children in schools; and (3) Impact of implementing cultural curricula on children's characters. The approach in writing this paper uses literature analysis with literature reviews and data is collected through systematic search of scientific literature on journal articles and documents that discuss significantly and are related to the theme of this research. The data that I get will be processed or analyzed descriptively, interpretatively and comparatively.